Variability of trace element content in human tooth sequences – a multivariate analysis - Szostek, Krzysztof (Anthropological Review, 1998)
Analyses of human bone material expand our knowledge of aspects of modern and historical population ecology, the etiology of diseases, reconstruction of historical diets, and the social and economic status of human groups. 35 adult lower jaw tooth sequences from the 17lh-century Cracow population were analysed. The skeletons were found in crypts of the medieval St. Mark’s church, following international standards. Levels of Pb, Zn, Cu and Cd were determined in undamaged permanent teeth PI, P2, Ml, M2 and M3, using anodic stripping voltammetry (ASV), while strontium concentrations were determined using AAS method. There were statistically significant differences in the levels of the analysed trace elements within the investigated tooth sequences. High interspecimen variability in the amount of accumulated microelements, probably resulting from nutritional, developmental and physiological stress, was also observed. The accumulation of Pb, Cd and Zn was the highest in M3 teeth and the lowest in M l. The results indicate that only one type of teeth should be used for intergroup and intragroup comparison of trace element content.